The Impact of Cross-National Distance on Survival of Foreign Subsidiaries - Fabio Cassio-de-Souza; Mario Henrique Ogasavara (BBR: Brazilian Business Review)
Survival of overseas subsidiaries is an important success indicator of foreign investments. Research on institutional approaches has been undertaken in this way, but generally restricted to a limited number of cross-national distances (CNDs). This research examines the impact of nine CNDs and local experience on subsidiary survival of foreign subsidiaries. Moreover, we tested the moderating effects of local experience on CND to analyze whether it could reduce these distances. Using a sample of 1,650 foreign subsidiaries established in 36 European countries, we applied Cox regression with a longitudinal analysis for the period 2007-2014. The results indicate that CND significantly affect subsidiary survival. Out of nine CND, four increase the risk of mortality, while one increases longevity. Local experience also plays a significant role for the continuity of the foreign operation in the local market, while moderating the impact between one CND and survival. These results can provide valuable information for strategic processes and better decision making of internationalization, and contribute to the success and survival of international operations.